The Influence of Creativity, Independence, and Leadership on Employee Performance at the Y Cooperative in Mojokerto - Setiawan, Erry; Setyaasih, Setyaasih; Perdana, Buyung Cahya; Sunaryo, Agus (International Journal of Integrative Sciences, 2024)
This research aims to determine the factors that influence the work of part-time employees or the majority of Cooperative Y in Mojokerto Regency, including work creativity, independence, and leadership abilities. The research method used in this research is a method using quantitative research methods. In this research, 31 Cooperative Y workers in Mojokerto Regency were interviewed. The sampling method is qualitative or statistical, i.e. the process of collecting data and looking in depth at various specified items. The data obtained were analyzed using multiple regression analysis using statistical models, especially the SPSS 25 (Statistical Package for Social Science 25) program. Based on the test results obtained using the SPSS 25 program, the following results were obtained. Often the linear regression equation is as follows. Y = -1.400 + 0.267X1 + 0.415X2 + 0.694X3. The variables innovation, independence and leadership influence employee performance at Cooperative Y, Mojokerto Regency. Differences in innovation, autonomy and leadership simultaneously influence employee performance at Cooperative Y in Mojokerto Regency. The control variable is the main industry of the Y Cooperative employees in Mojokerto Regency